SIMBOLISASI KEKERASAN DALAM RUMAH TANGGA (KDRT) DALAM KARYA FOTOGRAFI EKSPRESI - Zikri, Nasikhul Amin Al; Sahrul, Sahrul; Ediwar, Ediwar (Journal of Innovation Research and Knowledge, 2023)
The artwork discussed in this text is a photographic work that aims to express the artist's anxiety towards domestic violence. The use of symbols in the photographs helps to convey the message and raise awareness about this issue. The creation of the work involves the use of subjects, objects, photographic techniques, and digital editing to symbolize domestic violence. The artist incorporates their personal views and interpretations, drawing from their experiences, emotions, and observations related to domestic violence. The purpose of this artwork is to increase public awareness about domestic violence and inspire relevant parties to address the problem more effectively. Overall, the artist utilizes expression photography as a medium to disclose their emotions and to shed light on the issue of domestic violence.